Serum Bilirubin Levels in Overweight and Obese Individuals: The Importance of Anti-Inflammatory and Antioxidant Responses - Lovro Žiberna; Zala Jenko-Pražnikar; Ana Petelin (MDPI AG, 2021)
Obesity is a chronic condition involving low-grade inflammation and increased oxidative stress; thus, obese and overweight people have lower values of serum bilirubin. Essentially, bilirubin is a potent endogenous antioxidant molecule with anti-inflammatory, immunomodulatory, antithrombotic, and endocrine properties. This review paper presents the interplay between obesity-related pathological processes and bilirubin, with a focus on adipose tissue and adipokines. We discuss potential strategies to mildly increase serum bilirubin levels in obese patients as an adjunctive therapeutic approach.